Clinical feasibility of a new through‐the‐scope fully covered esophageal self‐expandable metallic stent: An in vivo animal study. Issue 1 (31st March 2013) - Cheon, Young Koog; Lee, Tae Yoon; Sung, In Kyung; Shim, Chan Sup
Abstract : Background: Most delivery devices used for esophageal stents for obstructing esophageal cancer have a diameter of 5–8 mm, a size that is too large to pass through the endoscopic working channel. The conventional esophageal stent requires multiple endoscopic procedures for implantation. The purpose of the present study was to evaluate the clinical feasibility of a newly developed fully covered, self‐expanding, through‐the‐scope (TTS) esophageal stent in a porcine model. Methods: Eight mini pigs were used. Each animal underwent placement of a fully covered TTS stent (Hanarostent® Esophagus TTS) and the upper part of the stent was fixed by suturing with nylon. Fluoroscopy was carried out every week to assess migration of the stent. Follow‐up endoscopy was done every month for 3 months to evaluate the status of the membrane, stent mesh, grade of tissue hyperplasia, and mucosal changes at both ends of the stent. Results: All stents were successfully and easily deployed, and were placed without any distortion in the stent or without rupture of the membrane. In two cases, stent migration was observed after 8 weeks. No case of membrane disruption, stent mesh disruption or tissue hyperplasia at either end of the stent was found at the completion of the study. Conclusion: Our findings indicate that the new fully covered self‐expanding TTS esophageal stent is easy and simple to implant, and no significant distortion of mesh or disruption of membrane was observed.